Environmental and techno‐economic evaluation of β‐carotene production from Dunaliella salina. A biorefinery approach. (23rd April 2019) - Espada, Juan J.; Pérez‐Antolín, Daniel; Vicente, Gemma; Bautista, Luis F.; Morales, Victoria; Rodríguez, Rosalía
Abstract: In this work, a solvent‐based extraction procedure and a procedure using supercritical CO2 to obtain β ‐carotene from Dunaliella salina were compared from environmental and economic perspectives. Both processes were simulated using a biorefinery scheme in which β ‐carotene was obtained and the waste biomass was used to produce energy. The results were used to carry out a life‐cycle assessment (LCA). The LCA results showed that a supercritical process was better in terms of energy consumption and greenhouse gas emissions. However, the low extraction yield of this technology makes it necessary to use large amounts of nutrients, whose production increases toxicity‐related impacts related to organic solvent extraction. This also affects the β ‐carotene price, which is twofold higher in the case of a supercritical extraction process‐based biorefinery. The results therefore indicate that the potential benefits of the supercritical process in terms of environmental issues do not balance the drawbacks related to its low extraction yield. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd